Co-metabolic enhancement of 1H-1, 2, 4-triazole biodegradation through nitrification. (January 2019) - Wu, Haobo; Sun, Qianqian; Sun, Yinglu; Zhou, Yukun; Wang, Jing; Hou, Cheng; Jiang, Xinbai; Liu, Xiaodong; Shen, Jinyou
Graphical abstract: Highlights: Co-metabolic enhancement of TZ biodegradation was achieved through nitrification. The link between enhanced TZ biodegradation and nitrification was established. A new co-metabolic pathway of TZ was proposed based on intermediate analysis. Functional species related to nitrification and biodegradation was enriched. Nitrification-assisted co-metabolism had a promising potential for TZ removal. Abstract: Due to highly recalcitrant nature of 1H-1, 2, 4-triazole (TZ), the conventional biological process is quite ineffective for TZ removal from wastewater. In this study, co-metabolic enhancement of TZ biodegradation through nitrification was investigated in an activated sludge reactor. The link between enhanced TZ degradation and nitrification was established through highly efficient removal of TZ, TOC as well as dissolved organic matter with the supplement of NH4 + . A new co-metabolic degradation pathway of TZ was proposed based on the identification of five co-metabolic intermediates, including 2, 4-dihydro-[1, 2, 4]triazol-3-one and [1, 2, 4]triazolidine-3, 5-dione. High-throughput sequencing analysis suggested the significant improvement of microbial community in the co-metabolic system in terms of richness, abundance and uniformity. Functional species related to nitrification and biodegradation was enriched with the supplement of NH4 +, confirming the key role of nitrification. This study demonstrated that nitrification-assisted co-metabolism had a promising potential for the removal of recalcitrant contaminants such as TZ from wastewater.